Access to finance for innovation: the role of venture capital and the stock market - Francesco Bogliacino; Matteo Lucchese (European Commission, Joint Research Centre (JRC), 2011)
Financial constraints for young and small firms can prevent them from supporting innovation and employment creation. We analyze two of the various institutional mechanisms which have been proposed to circumvent it: the development of venture capital market and the stock market access. We will use the information provided by two Scoreboards - used to monitor innovative activity in Europe: the Innovation Union Scoreboard and the R&D Scoreboard. With the first, we study the determinants of the venture capital/GDP intensity in Europe. With the second, we try to assess the contribution of stock market to R&D investment. In the first part, we show that venture capital market complements structural feature such as R&D intensity and market capitalization, is more volatile and seems not affected by anticompetitive regulations. In the second part, we show that unlisted SMEs are more research intensive.
Keywords: M13; O31; O38; 330; Venture Capital; R&D; European Policy; Random Effect; Propensity Score Matching.